PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UN CYBERCAFE EN LA CIUDADELA SHUSHUHUAYCO DE LA CIUDAD DE LOJA - ZARAGOCÍN MARTÍNEZ, DIEGO ALFONSO (2016)
This thesis was conducted with the objective of providing the inhabitants of the citadel Shushuhuayco a place where Internet access and additional services counting personal attention to our clients or users. For this subsequent investigation was conducted which could see one of the major causes was considered the beginning of this project is the need in the citadel of having this service , is a populated area but away from the city center . The mounting location for the cyber cafe is a busy area in the citadel , and that there is a cyber close but has few machines and their attention is not constant, this information is way better advice designed a survey for the which conducted a field survey in order to get a sample, of which 221 candidates were drawn between men and women of all ages , where 215 of the respondents noted that they use the internet service, which is of this study , the purpose is that they facilitate the development of tasks that require the use of this . To others that this project will contribute to the economic growth of our city, achieving better income, and provide greater cash flow that will maintain and increase proper local economy that gradually will start at different ways to exploit the resources and business ideas that involve running, encouraging entrepreneurship human talent. The feasibility of creating this cyber cafe, this will was made according to four objectives of the project such as: market research, technical, financial and organizational. Before starting the development study was contextualized in the introduction briefly described and provided a focus on how prepared the study in general, made a sketch of what will be the document so that the reader can understand. In the development process of the study were conducted objectives served to anticipate the results of knowledge expected from the end of the research process. To meet the objectives and methods were applied to facilitate research techniques as they meet all the objectives. In the developed market study Universidad Nacional de Loja ~ 6 ~ research in guiding the project stages from conception , measurement of demand , which is offering 14,144 hours for the first year according to the bidder , unmet potential demand where we used the method of the survey of the residents of this area of the city of Loja and interview applied to competition, obtaining a result of 69,967 hours for the first year as the unmet demand , demonstrating the possibilities of entering the market and price analysis methods based on the average market costs and where to set the price of $ 0.80 cents with which you can acquire this service. The data obtained were applied to the results. The technical study focused primarily on the location of the cyber cafe and factors to perform quality service, the elements to be considered are: the plant capacity will be 8 computers, distribution of areas, and description of the process, selection of equipment and materials and labor. We developed an organizational study was presented where an organizational structure through flowcharts describing hierarchical levels , departments and staff roles they will play their respective offices , as well as what constituted the cyber world, which made it possible visualize clearly and precisely the approach that the company has. Developed financial analysis of installing the cyber cafe, through tools financial accounting purposes of determining whether it is profitable carry out the project, applying the indicator of net present value (NPV) were scored positive because in the 5th year life of the project is established profitable q is 436.24 USD. Likewise with the indicator of capital recovery period (PRC) we get the time in which to recover the initial investment and this acceptable as it is within the lifetime of the project, which would recover in two years 11 months and 4days. To measure the performance you get for every dollar, we used the cost-benefit ratio (B/C) , obtaining a result 1.18 which means that the ratio is greater than 1 indicating that the project is profitable . With the data obtained in the internal rate of return (IRR) can be mentioned that the company has a yield of 17.35%, making it feasible to invest. In terms of sensitivity the company supports the 6% Universidad Nacional de Loja ~ 7 ~ increases in costs and revenues decreased 5.09% Company supports future if the company suffers decline in sales. It released the economic situation and the initial investment is $ 7,586.89 of which 56.50 % run by the owner and the other part being financed by a bank, where he could display a short investment term. We developed a financial evaluation results with what we noted that generates profits. Finally conclusions are made in summary form , the results and knowledge reacher during development and analyzes on the subject , also took shape according to the recommendations in its project to improve and expand the business.